Measuring neurodevelopment in low-resource settings - Gladstone, M; Abubakar, A; Idro, R; Langfitt, J; Newton, C (Elsevier, 2017)
The burden of neurodevelopmental, cognitive, behavioural, and mental health disorders in children will continue to rise as infant and child mortality is reduced with improvements in medical care.1 In recognition of this epidemiological transition, the international community is shifting the focus from child survival to so-called child thrival, with the aim of supporting children to fulfil their developmental potential and promote their wellbeing. This transition is encapsulated in the WHO Global Strategy for Women’s, Children’s, and Adolescent’s Health 2016–2030: to survive, thrive, and transform. The new Sustainable Development Goals (SDGs) now include a focus on early child development (SDG4) to address this goal.2 In the past 10 years, funding agencies have increased spending on large-scale studies on the underlying causes and epidemiology of these disorders, and on interventional research to improve outcomes. In doing so, researchers and clinicians working in lowincome and middle-income countries (LMICs) require reliable and valid tools to screen, identify, and assess children in their local settings.